INNOVATIVE THERAPIES IN GENETIC DISEASES: SPINAL MUSCULAR ATROPHY - Elena-Silvia Shelby; Andrada Mirea (Amaltea Medical Publishing House, 2021)
Spinal muscular atrophy is a congenital neuromuscular disease characterized by the deterioration of the motor neurons located mainly in the anterior horns of the spinal cord, leading to progressive muscle weakness and atrophy. Globally, SMA is, after cystic fibrosis, the second cause of death due to a a genetic disease in the pediatric population. Over 95% of the total cases of SMA are represented by 5q SMA, caused by biallelic mutations in the SMN1 gene (5q13.2), the rest of the SMA types being called, generically, non-5q SMA. Currently, a few genetic targeted therapies are available for 5q SMA, while other innovative therapies are still in clinical trials. Early diagnosis and treatment of 5q SMA have an essential role in preventing the onset and evolution of symptoms and can save the life of the patient and prevent debilitating sequelae. This article aims to briefly describe the cause and symptomatology of 5q SMA as well as to make a short review of the genetic therapies available for this disease.